2015
DOI: 10.4049/jimmunol.1402037
|View full text |Cite
|
Sign up to set email alerts
|

Ly6Chigh Monocytes Control Cerebral Toxoplasmosis

Abstract: Cerebral infection with the parasite Toxoplasma gondii is followed by activation of resident cells and recruitment of immune cells from the periphery to the CNS. In this study, we show that a subset of myeloid cells, namely Ly6ChighCCR2+ inflammatory monocytes that infiltrate the brain upon chronic T. gondii infection, plays a decisive role in host defense. Depletion of this monocyte subset resulted in elevated parasite load and decreased survival of infected mice, suggesting their crucial role. Notably, Ly6Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 100 publications
(138 citation statements)
references
References 85 publications
9
125
1
1
Order By: Relevance
“…In the chronic stage of the infection, brain resident microglia cells displayed an activated phenotype, and peripheral immune cells including CD11b − lymphoid and CD11b + myeloid cells infiltrated the brain. In line with previous reports, characterization of brain immune cells revealed that recruited CD11b + myeloid cells contained Ly6G − inflammatory monocytes and Ly6G + neutrophil granulocytes (Möhle et al, 2014; Biswas et al, 2015). Despite low absolute numbers of neutrophils in the chronic stage, they form a substantial portion of the myeloid cell compartment in the CNS in the acute stage of the infection.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the chronic stage of the infection, brain resident microglia cells displayed an activated phenotype, and peripheral immune cells including CD11b − lymphoid and CD11b + myeloid cells infiltrated the brain. In line with previous reports, characterization of brain immune cells revealed that recruited CD11b + myeloid cells contained Ly6G − inflammatory monocytes and Ly6G + neutrophil granulocytes (Möhle et al, 2014; Biswas et al, 2015). Despite low absolute numbers of neutrophils in the chronic stage, they form a substantial portion of the myeloid cell compartment in the CNS in the acute stage of the infection.…”
Section: Discussionsupporting
confidence: 89%
“…Alongside the enhanced egress of immune cells in the periphery, cerebral toxoplasmosis leads to the activation of brain resident cells and infiltration of circulating immune cells to the CNS (Möhle et al, 2014; Biswas et al, 2015). Peripheral immune cell influx into the infected brain is characterized by initial invasion of neutrophils, followed by the recruitment of BM-derived monocytes and the lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations